Artificial Intelligence-Based Tools in Research Writing : Current Trends and Future Potentials - Donnie, Adams; Chuah, Kee Man (CRC Press, Routledge, 2023)
Questions begin to arise around to what extent research writing and training can be supported electronically. The emergence of Artificial Intelligence (AI) technologies have triggered a tremendous interest among educational technologists. One area that has received much attention is AI-based tools, developed to assist researchers in the writing process. AI-powered writing tools aim to not only ease the process of research writing but also to enhance the quality of critical analysis particularly in the aspect of literature review and language style. Despite the trends in adopting AI components within research writing, there are still-limited efforts to examine its implementation, strengths and weaknesses. This chapter reviews some of the key studies concerning AI in research writing as well as an extensive review of existing tools by covering their AI-based features, affordances and constraints. The chapter also includes a discussion on the future potentials of AI implementation with regard to research writing. This chapter would serve as a good reference to uncover the hidden potentials of AI-based tools in assisting students to produce high-quality research writing.